THE ARTISTIC FUNCTION OF EPITHETES IN KENESBAY KARIMOV'S POETRY (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In the article, opinions and analyses regarding epithets in the poetry of K. Karimov and their artistic merit are based on scientific and theoretical works.